MEMBANGUN HUKUM BERBASIS NILAI-NILAI INDONESIA (TINJAUAN PRISMATIKA HUKUM SEBAGAI DASAR PEMBANGUNAN HUKUM DI INDONESIA BERBASIS PANCASILA) - Purnawan D Negara (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
In legal development in Indonesia there is still a lot of colonial laws that are applied, whose values a re not rooted in Indonesian society. National Legal Seminar VI in 1994 in Jakarta said that the law of a nation must be